Loss expression of micro ribonucleic acid (miRNA)‐200c induces adverse post‐surgical prognosis of advanced stage non‐small cell lung carcinoma and its potential relationship with ETAR messenger RNA. Issue 4 (July 2015) - Zhao, Jinpeng; Zhao, Yandong; Wang, Zizong; Xuan, Yunpeng; Luo, Yiren; Jiao, Wenjie
Abstract Background Non‐small cell lung cancer (NSCLC) is the leading cause of cancer mortality worldwide. As micro ribonucleic acid (miRNA)‐200 and ETAR may play an essential role in the process of epithelial to mesenchymal transition (EMT) simultaneously, the purpose of this study was to detect the expression of miRNA‐200c and ETAR messenger (m)RNA and assess their prognostic significance in early stage NSCLC. Methods Our study included 78 advanced stage (IIB, IIIA, IIIB) NSCLC patients. All patients were smokers. Using quantitative reverse transcriptase polymerase chain reaction analysis, we detected the expression of miRNA‐200c and ETAR mRNA and assessed their correlation by χ2 test. Time to progression was used as the recurrent index and was assessed by univariate and multivariate analysis in the Cox hazard model. Results Both miRNA‐200c and ETAR mRNA expression are associated with N stage and tumor node metastasis (TNM) stage in a series of advanced NSCLC patients. Among N stage and TNM stage patients, significant differences were found in IIB (P = 0.0126), IIIB (P = 0.0107) and N0 (P = 0.0023) and in N1 + N2 groups (P = 0.0133). Using both univariate and multivariate survival analyses, we found that miRNA‐200c (hazard ratio [HR] = 0.352, 95% confidence interval [CI]: 0.187–0.662) and ETAR mRNA (HR = 2.500 95% CI: 1.345–4.647) were independent prognostic factors, independent of TNM stage (HR = 2.414, 95% CI: 1.600–3.642) and differentiation (HR = 1.530, 95% CI: 1.050–2230). Conclusions miRNA‐200c induces an expedient surgical survival, whereas ETAR mRNA has the reverse prognosis in advanced stage NSCLC patients. A potential relationship exists in that miRNA‐200c targets ETAR mRNA during EMT.